Navigating Interfaith Dynamics: A Sociohistorical Overview of the Encounter Between Monk Bahira and the Young Prophet Muhammad - Lumban Gaol, Ebeneser (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This study examines the encounter between Bahira, a Syrian Christian monk, and the young Prophet Muhammad within the socio-religious historical context of 6th-century Arabia. The aim of this research is to analyze the historical, social, and religious context of the time and its significance for interfaith relations in the contemporary era. The study employs a historical method with a socio-historical approach. The research provides a description of the encounter between the two figures, which took place in the city of Busrā, Syria, when the young prophet accompanied a caravan led by his uncle, Abu Talib. During this meeting, Bahira engaged in dialogue with the prophet and identified a sign of prophethood on his shoulder. Although there is ongoing debate among Christian and Islamic scholars regarding the historicity of this event, the narrative of the encounter offers a positive contribution to shaping a new perspective on the history of Muslim-Christian relations. The meeting between Bahira and the young Prophet Muhammad serves as a model for contemporary discourse on religious coexistence, emphasizing common ground, hospitality and mutual respect, pluralistic dialogue, and reciprocal recognition. Through these aspects, the encounter illustrates dialogue and tolerance among adherents of different faiths. This study contributes to historical discourse on interfaith dynamics and highlights the importance of exploring religious historical narratives to foster interfaith cooperation.